ANALISA HUBUNGAN ANTARA GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, BUDAYA ORGANISASI, DAN KINERJA GURU DI SEKOLAH MENENGAH ATAS SE-KECAMATAN PAMULANG - Annisa Nurul Inaya; Estiningsih Trihandayani; Akhirudin (STKIP Subang, 2026)
This study aims to analyze the relationship between transformational leadership style, work motivation, and organizational culture with teacher performance in Senior High Schools throughout Pamulang District. This research employed a quantitative approach using a correlational research design. The population consisted of 304 teachers from public and private senior high schools in Pamulang District, with a sample of 176 teachers selected through proportional random sampling. Data were collected using questionnaires developed based on the indicators of each variable and measured using a five-point Likert scale. Prior to data analysis, the instruments were tested for validity and reliability, while the data were examined through normality and homogeneity tests. Data analysis was conducted using Pearson Product Moment correlation and multiple linear regression analysis to determine the relationship and contribution of the independent variables to teacher performance. The findings indicate that transformational leadership style, work motivation, and organizational culture have a positive and significant relationship with teacher performance, both partially and simultaneously. These variables contribute significantly to improving teachers' professional performance. Therefore, schools need to strengthen transformational leadership practices, enhance teachers' work motivation, and develop a positive organizational culture to improve teacher performance and educational quality.